Brand Awareness Strategy for Fashion Urban Youth Local Brand "Pinx Project" - Insania, Rima; Mutiaz, Intan Rizky (The Indonesian Journal of Business Administration, 2013)
Indonesian young designers have a very strong potential to explore the international level with the achievements that gradually starts to open the eyes of the global fashion world.urban youth local label movement which spreading in 5 years, glance indonesia fashion industry. One of the is Pinx Project. Pinx Project, found in late November 2011, grew along with urban youth fashion which was booming among young people and many other emerging fashion lines. Pinx, which can still be considered as freshman in the field of urban youth fashion, has to compete intensely with other fashion lines, causing its brand awareness to still be under the surface. Together with Mannequin Plastic, Pinx participated in fashion events in the same booth, so consumer’s perception is that Pinx is part of Mannequin Plastic. This was done due to the difficulty of curation to attend a fashion event. This cause low brand awareness of Pinx and causing Pinx still under surface in urban youth fashion industry. From internal and external analysis, the efectiveness marketing was developed by pinx n 3 years considered can delivered message to costumer yet. This causing few problems are low distribution coverage, low quality of packaging, low durability of product style, low promotion (visual), low information source, less special program and highly competitive rivalry and subtitutes among urban youth brand. Strategy used to gaining brand awareness is Intergrated marketing communication and Product development strategy. Product development strategy using for involve new category market, cause Pinx already into apparel market with their highly competitor. The implementation of this strategy are Intergrated marketing communication and Product development strategy for the next mid-term strategy for Pinx are more visula promotion, adding more product placing in concept store, webstore development and also product placement in departemen store. This strategy expexted to gaining brand awareness and boosting revenue sales in every month. The strategy expected can be in implanted and helps the company to raise awareness brand and market share.